Cancer Surveillance and Preventive Services in a Diverse Sample of Breast and Colorectal Cancer Survivors - Glenn, Beth A. (J Cancer Surviv, 2020)
PURPOSE: Cancer survivors diagnosed at an early age remain at risk for cancer recurrence and other chronic diseases. This study assessed engagement in surveillance for recurrence, cancer screening, and other recommended preventive health services among breast and colorectal cancer survivors with early onset disease (≤ 50 years) who were diagnosed in California. METHODS: Breast and colorectal cancer survivors diagnosed with early-onset cancer between 1999–2009 were identified through the California Cancer Registry, the state-based cancer registry, and surveyed. Multivariable regression analyses were used to assess correlates of receipt of cancer surveillance, cancer screening, and other preventive health services. RESULTS: Of the 497 survivors that were invited to participate in the study, 156 completed the survey for a response rate of 31%. The sample was 50 years of age on average (range 32–69 years) with a mean time since diagnosis of 9 years. The majority of the sample (71%) was a racial/ethnic minority (24% Latino, 15% African American, 29% Asian). Overall, 80% received appropriate surveillance for recurrence, and 72% received recommended screening for early detection of other cancers (breast, cervical, colorectal). Increasing age was associated with lower likelihood of early detection screening (adjusted odds ratio [aOR] 0.28, 95% confidence interval [CI] 0.11 – 0.69), and higher income was associated with a greater likelihood (aOR 4.89, 95% CI 1.62 – 14.81). Screening rates were highest for blood pressure (96%), cholesterol (86%), and diabetes (81%), followed by dental visits (64%) and flu vaccination (35%). Greater use of recommended preventive health services was associated with increasing age, female sex, higher education level, and having health insurance. CONCLUSIONS: Although the majority of survivors received appropriate surveillance for recurrence, engagement in other preventive health services varied substantially. IMPLICATIONS FOR CANCER SURVIVORS: Efforts are needed to address gaps in use of recommended cancer screening and preventive health services among cancer survivors, particularly survivors with early onset disease who may be at increased risk for additional cancers and common chronic conditions over their lifetime.